Pemberdayaan dan Pendampingan Digitalisasi Kampung Berbasis Website Sebagai Upaya Meningkatkan Potensi Kampung - Okto Irianto; Henie Poerwandar Asmaningrum; Adi Maulana Rachman; Tini Adiatma (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Digital marketing is a combination of interactive and integrated marketing that facilitates interaction between producers, market intermediaries and potential consumers. This digital marketing strategy is more prospective because it allows potential customers to obtain all kinds of information about products and make transactions via the internet. This community service program is carried out at ECA High School which is located in Nasai Village, which is one of the villages supported by Musamus University. Program implementation consists of observation, core activities, and evaluation. The results of this community service program were the creation of the ECA Online Market website and its management guidebook, achieving an increase in program participants' understanding of 0.3359 in the medium category, as well as a participant satisfaction response of 72.28% in the very satisfied category. In conclusion, the community service program ran smoothly and provided results as expected.